Hubungan Status Gizi, Konsumsi Junk Food, dan Kebiasaan Berolahraga Remaja Perempuan di Jakarta dengan Kejadian Dismenorea Primer: Hubungan antara Status Gizi, Konsumsi Junk Food, dan Kebiasaan Olahraga Remaja Perempuan di Jakarta dengan Kejadian Dismenorea Primer - Primalova, Ariela; Stefani, Megah (Amerta Nutrition, 2024)
Background: Every one in six people in the world is an adolescent, and as many as 85% of adolescents live in developed countries, which often experience menstrual disorders such as primary dysmenorrhea. Primary dysmenorrhea is menstrual pain in the absence of pathological conditions in the pelvis that often occurs at a young/adolescent age triggered by various factors such as nutritional status, diet, exercise habits, and stress. Objectives: To analyze the association between nutritional status (BMI-for-age), junk food consumption, and exercise habits of adolescent girls in Jakarta with the incidence of primary dysmenorrhea. Methods: This study used a cross-sectional design, the population of this study was all grade 11 students in Jakarta (East Jakarta, South Jakarta, West Jakarta, Central Jakarta, North Jakarta). The method of obtaining samples used was purposive sampling. The instrument used was a questionnaire regarding nutritional status, exercise habits and junk food consumption patterns assessed using the Food Frequency Questionnaire (FFQ) through Google Forms. Results: The results showed a significant relationship between nutritional status (p = 0.022), junk food consumption (p = 0.000), and exercise habits (p = 0.000) with the incidence of primary dysmenorrhea. Conclusions: There was a correlation between nutritional status, junk food consumption, and exercise habits on the incidence of primary dysmenorrhea in adolescent girls in Jakarta. Further research is needed on the relationship between nutritional status, junk food consumption and exercise habits with the incidence of primary dysmenorrhea in other age groups, and with different methods to expand knowledge related to factors that cause primary dysmenorrhea.